Predicting municipal solid waste using a coupled artificial neural network with archimedes optimisation algorithm and socioeconomic components - Liang G.; Panahi F.; Ahmed A.N.; Ehteram M.; Band S.S.; Elshafie A. (Elsevier Ltd, 2023)
Forecasting; Genetic algorithms; Health risks; Mean square error; Model structures; Municipal solid waste; Particle swarm optimization (PSO); 'current; Fuzzy reasoning; Inclusive multiple model; Multiple-modeling; Neural-networks; Optimization algorithms; Particle swarm; Sine-cosine algorithm; Solid waste generation; Swarm optimization; Neural networks